A comparative study on health quotient of nursing students before and after the clinical internship (护理专业学生实习前后健康商数状况的对比研究) - WANG Huiying (王慧颖); ZHOU Fang (周芳); LI Ru (李茹) (中西医结合护理)
Objective To investigate the influence of internship at the health management center of a hospital on health quotient of nursing students, and explore ways of developing students’ health awareness. Methods A total of 160 nursing students were investigated with Health Quotient Modified Questionnaire, and changes in health quotient level were analyzed before and after internship. Results Nursing students achieved higher scores of self-care, health knowledge, life skills and mental status dimension at the end of internship (P＜0. 05). There was no significant difference in living habits dimension before and after internship (P＞0. 05). Conclusion Professional health guidance and training and enhanced clinical practice during internship contribute to the health quotient improvement among nursing students. (目的 探讨在健康管理中心实习对护理专业实习生健康商数(健商)的影响, 探索培养学生健康意识的途径。方法 采用健康商数修正版问卷收集资料, 分别在实习前和实习后进行调查, 分析160名护理专业实习生健商状况。结果 实习后, 160名护理专业实习生自我保健、健康知识、生活技能、精神状态维度评分结果较实习前提高, 差异有统计学意义(P＜0. 05), 生活方式维度评分改变的差异无统计学意义(P＞0. 05)。结论 通过开展专业的健康指导和培养, 强化临床实习培养, 有助于提升护理专业实习生健商。)